Short‐term outcomes of robotic‐assisted surgery following neoadjuvant chemotherapy for lower rectal cancer. Issue 3 (18th March 2022) - Morohashi, Hajime; Sakamoto, Yoshiyuki; Miura, Takuya; Ichinohe, Daichi; Kubota, Shunsuke; Yamazaki, Keisuke; Ichisawa, Aika; Mitsuhashi, Yuto; Wakiya, Taiichi; Hakamada, Kenichi
Abstract: Introduction: There have been reports about robotic surgery for rectal cancer with chemoradiotherapy (CRT), but only a few studies have compared the use of robotic surgery with and without neoadjuvant chemotherapy (NAC). The aim of our study was to compare the perioperative outcomes of robotic surgery with and without NAC for lower rectal cancer and to examine the effects of NAC on robotic surgery. Methods: From January 2016 to July 2021, we compared the short‐term outcomes of 45 patients who did not undergo NAC and 55 patients who underwent NAC. Results: The rate of sphincter‐preserving surgeries was higher in the NAC group than in the non‐NAC group ( P  = .024). The total operative time was significantly longer in the NAC group than in the non‐NAC group ( P  < .001). The rate of lateral lymph node dissection was significantly higher in the NAC group than in the non‐NAC group ( P  < .001). No significant differences were identified in the rate of incisional surgical site infections (SSI), organ/space SSI postoperative bleeding, small bowel obstruction, anastomotic leakage, urinary dysfunction, or urinary infections between the groups. There were eight incidences of lateral lymph node metastasis (15%) and two cases with positive resection margins (4.0%) in the NAC group. Conclusions: Robotic surgery after NAC has few complications and a higher sphincter‐preserving rate that without NAC.